2022
DOI: 10.1089/jpm.2021.0596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Pain Management Practices for Cancer Patients among Health Professionals: A Global Survey

Abstract: Background:Cancer incidence in the world is predicted to increase in the next decade. While progress has been in diagnosis and treatment, much is still remains to be done to improve cancer pain therapy, mainly in underserved communities in low income countries.Objective: To determine knowledge, beliefs and barriers regarding pain management in both high and low income countries (according to the WHO classification); and to learn about ways to improve the current state of affairs. Design: Descriptive surveySett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The observed decrease in cancer pain prevalence and pain severity may also be positively impacted by raised awareness and knowledge of healthcare professionals about cancer pain treatment and the publication of new pain therapy guidelines [26,27]. However, there is still room for improvement as the literature indicates that there is a difference in knowledge between healthcare professionals and among professionals from different countries [317,318]. Our results showed that the prevalence of cancer pain was significantly higher in South America, Asia and Africa than in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed decrease in cancer pain prevalence and pain severity may also be positively impacted by raised awareness and knowledge of healthcare professionals about cancer pain treatment and the publication of new pain therapy guidelines [26,27]. However, there is still room for improvement as the literature indicates that there is a difference in knowledge between healthcare professionals and among professionals from different countries [317,318]. Our results showed that the prevalence of cancer pain was significantly higher in South America, Asia and Africa than in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the prevalence of cancer pain was significantly higher in South America, Asia and Africa than in Europe. Silbermann and colleagues have shown that the majority of patients with cancer in low-income countries are undertreated for their pain, partly due to a lack of appropriate education [318]. Furthermore, compared with nurses, physicians have more knowledge about pain management, while both lack knowledge regarding the side effects and pharmacology of opioids [317].…”
Section: Discussionmentioning
confidence: 99%
“…This raises questions regarding the generalizability of the study findings and may reflect global disparities in access to, and use of, opioid analgesics for cancer pain. One global survey in 2022 involving 56 countries across six WHO regions (Africa, the Americas, South East Asia, Eastern Mediterranean, Europe, and Western Pacific) reported that consumption of opioids (in MME per capita) was highest in the Americas (22.0 MME per capita) and Europe (13.8 MME per capita) and lowest in the African, South East Asian, Eastern Mediterranean, and Western Pacific regions (range, 0.21–0.73 MME per capita) 280 . Another study also from 2022 reported a substantially lower defined daily dose (the average maintenance dose of opioid analgesic per day) in people with cancer in 31 low‐to‐middle income countries (ranging from a median of 0 in countries such as Yemen, Cameroon, Eritrea, Nigeria, to 9 in countries such as Sudan, Myanmar, Pakistan, and Iraq) compared with a median of 69 based on worldwide defined daily dose data estimates 281 .…”
Section: Discussionmentioning
confidence: 99%
“…Optymizm odnoszący się do tak znacznego postępu jest jak najbardziej uzasadniony, jednak należy pamiętać o istniejących nadal barierach w leczeniu bólu zamykających wielu chorym możliwość właściwego łagodzenia cierpienia. Brak dostępności opioidów jest powszechnym problemem w wielu krajach, a niewystarczające leczenie bólu umiarkowanego i silnego wydaje się problemem nawet w krajach o dobrze funkcjonującym systemie ochrony zdrowia [4,5]. Zagadnienie bezpiecznej terapii przy zastosowaniu opioidów nabrało dodatkowo znaczenia w świetle powikłań toksycznych (w tym wielu śmiertelnych), które miały miejsce w ostatnich latach w Stanach Zjednoczonych i innych krajach w związku z niewłaściwym stosowaniem leków opioidowych (zjawisko znane jako kryzys opioidowy) [6].…”
Section: Wstępunclassified